Ayurvedic Management of Ashmari (Nephrolithiasis) - Bishnupriya Mohanty; Shubhada Lekurwale; Abhishek Santosh Shriramjwar (International Journal of Ayurveda and Pharma Research, 2024)
Mutrashmari is one among the Asta Mahagada (eight fatal conditions) due to involvement of Basti, which is one of Trimarma and difficult to cure. It is Kapha Pradhana Tridoshaja Vyadhi due to clinical resemblance in clinical manifestation, Mutrashmari is compared to nephro-lithiasis or uro-lithiasis. Nephro-lithiasis is pathological condition of the urinary crystalloids takes place anywhere in the urinary tract. It is a big challenge for all health care systems. Because of changes in lifestyle, dietary habits, and treatment modalities its incidence and prevalence have increased significantly over the past few decades. Prevalence rate of kidney stone is about 11% in males and 9% in females, other diseases such as high blood pressure; diabetes and obesity may increase the risk for kidney stones. In Ayurveda, Basti Chikista is best for any obstruction or Sroto-Sanga in the body especially in the Sthana of Vata Dosha as Pakwashya (the main Sthana of Vata Dosha). Properties like Teekshna, Ushna and Shothaghna, Mutra Virechaniya Karma helps to eliminate the stone from urinary system and restore its functions. In the present case both Shodhana and Shamana Chikista were adopted. Nabhi Purana with Ardraka Swarasa reduced the colicky pain by pacifying the Sthanika Vata Dosha. Mutra Virechaniya (diuretic), Ashmarighna (litho-triptic) and Shophaghna (anti-inflammatory) are the way to reduce symptoms of renal stones. These medicines and therapeutics also helps to prevent recurrence.